A study to restriction the plant species of the vegetation cover on the sandy coastal strip in the western region of Libya in Zwarah, Misratah and Surt - Sharashy, Omar (Journal of Pure & Applied Sciences, 2017)
The species  distribution  reflects  the  effects  of  several  factors at different scales. Climate, topography and  soil  are  thought to exert influences on the plant distribution at  region  and  landscape.  Much of   indigenous  vegetation   of    Libya   consists   of surviving  remnants  of  more  favorable  climate  age. The  flora of   the  coastal  sand dune  varies  in accordance  with  the  vegetational  zone  of  Libya.  Real  dune plants not  only   tolerate    burial  in  sand, but   demand  it  in order to  retain  their   vitality. the coastal  sand  dune  vegetation  in the western region  of  Libya are comparatively rich in the number of species. The results  of  the  physical  analysis  of  soil in the studied sites generally was coarse sand, the  results  of  chemical  analysis  showed  that,  the   soil  content   of  minerals / elements  there  were  differences  between   the  three  sites  were  recorded  in  Surt higher  value   in  Na  compared   to   the   other  two   sites  were   211.5   ppm  while  Zwarah   and  Misratah  153.3  and  88.67   ppm. While  as Soil   content  of   organic matter at  the site of Surt  was the lowest amount  reached  to  0.09 %  compared  with its Zwarah  and Misratah 0.16 % and 0.25 % respectively. The  results  revealed  that , the  number of families 20 and 44  genus, and  53 species, included  26  annual   herbs;  24  perennial   herbs  and  3  species  biennial   herb. The highest   percentage   contribution   of   annual   herbs  was   recorded   in  the   coastal sand    dune   habitat    of  Surt   46 %,  while  the   highest percentage contribution  of perennial herbs  was recorded  in  the  coastal sand  dune  habitat  of  Zwarah  reached 46 %. The  flora  of  Libya  is  not   rich   in   the  number  of   species , the  landscape comprises  the richest   vegetation and   the  highest   number   of  species   known   from Libya. Study of   local  plant  species  in  their  habitats,  the  aim  is  to  know the factors and conditions   that   control   their   growth   and  distribution,  and   thus   to   know   the composition of plant communities in these environments.